Spontaneous calcified cerebral emboli: a comprehensive review and proposed diagnostic criteria - Menounos, Spiro; Matar, Walid (Frontiers in Neurology, 2024)
Spontaneous calcified cerebral emboli (SCCE) secondary to aortic valve calcification are a rare and underreported cause of acute ischaemic stroke. Only five cases of SCCE secondary to bicuspid aortic valve calcification have been reported in the literature. This review includes a unique case example of acute ischaemic stroke secondary to SCCE, as the first manifestation of a calcified bicuspid aortic valve. This is the first clinical case of calcified cerebral emboli (CCE) associated with borderzone infarction (‘cortical ribbon sign’). Whilst previously assumed that most CCE are secondary to iatrogenic causes, recent literature suggests the majority of CCE are spontaneous and clinically silent. Despite CT imaging widely considered the ‘gold standard’ for diagnosis, CCE are frequently misdiagnosed and missed entirely. Misdiagnosis of CCE may have catastrophic consequences due to the high risk of recurrence and missed opportunity to prevent neurological disability and death. This review presents a revised CCE diagnostic criteria, using evidence that has emerged over the last decade to create both Compulsory (Major) and Supporting (Minor) criteria. Current CCE management is not evidence based and remains largely speculative. SCCE may be the first manifestation of cardiac or vascular disease and diagnosis should trigger aggressive treatment of emboligenic sources. Future epidemiological studies, analysing symptomatic and asymptomatic SCCE patients, would be beneficial in providing accurate quantification of disease burden. Other future research directions include exploring intracranial stenting for CCE revascularisation and cerebral intravascular lithotripsy.